Does nail size or difference between canal and nail diameter influence likelihood of union or time to union of femoral shaft fractures treated with intramedullary nailing? A retrospective cohort study - Shih, Chiu-Yu; Kor, Chew-Teng; Hsieh, Cheng-Pu; Chen, Chiu-Liang; Lo, Yu-Cheng (BMC musculoskeletal disorders, 2022)
Background This study aims to determine whether nail size or the difference between canal and nail diameter (CN difference) affects the union rate and time of femoral shaft fracture treated with an interlocking intramedullary nail (IMN). Methods This was a retrospective review of 257 patients with femoral shaft fractures treated with IMN at a tertiary trauma medical center. All the IMN inserted were the same (Stryker T2 Femoral Nail). The patients were divided into groups based on nail size (10-, 11-, 12-, or 13-mm) and CN difference (< 1, 1-2, or > 2 mm), and union rate and time to union were compared. Results The 10-, 11-, 12-, and 13-mm groups based on nail size had 113, 74, 54, and 16 patients, respectively. The overall union rate was 97% (257/265). No significant differences in union rate or time to union were observed among these 4 groups. The groups based on CN differences of < 1-, 1 to 2, and > 2 mm comprised 143, 79, and 35 patients, respectively. Again, no significant differences were noted in union rate or mean time to union among the groups. Conclusions Similar union rate and time to union were observed, regardless of nail size or CN difference. This finding indicates that most simple femoral shaft fractures can be treated with a standard, reamed 10-mm IMN. A larger nail insertion is unnecessary and presents more risks; comparatively, the use of a small nail with less reaming is simpler, requires shorter operative times, results in less blood loss, and is less expensive. Keywords: Femoral fracture, Fracture Fixation, Intramedullary, Nailing, Intramedullary, Fractures, Ununited, Fractures, Malunited